PERLINDUNGAN HUKUM BAGI KONSUMEN YANG BERITIKAD BAIK DALAM PEMBELIAN APARTEMEN (STUDI PUTUSAN : NO. 697/Pdt.G/2018/PN.Jkt.Utr) - Monica Monica; Ermanto Fahamsyah (Fakultas Hukum Universitas Tarumanagara, 2020)
Legal protection is a protection given to business actors as well as consumers who have goodwill in entering into an agreement. This agreement’s about agreement on buying and selling an apartment. In this agreement, consumers who have goodwill from the beginning until the end of the agreement.therefore as a customer with goodwill they need to get a legal protection. This legal protection can be formed of legal protection that has been regulated in the UUPK and SEMA. The UUPK itself explains that as consumers in goodwill will get protectionif this consumer has performed all their obligations. Unfortunately, the rights that should be obtained have been violated by the business actorinstead. Meanwhile, according to SEMA who also asserted that the consume hasme the criteria of consumers in goodwill according toprovisions Pasal 1338 ayat (3) KUH Per, then they will get legal support which in this case a legal protection. However, it is not only possible to ask for legal protection of their violated rights, as a consumer they can also ask for accountability and compensation for what they have experienced, this matter has been regarded specifically regulated in both the UUPK and KUH Per. This liability is more the responsibility based on the existence of an element of error or default, liability based on the contract (agreement), or direct accountability by the producer for the loss suffered by the consumer.While the compensation must be following the losses suffered by consumers who already have goodwill, or even compensation accordance to the provisions of the Act, KUH Per.